A method for preparing a hollow nanorod-shaped iridium oxide catalyst with a burr structure suitable for oxygen electrolysis in acidic water.

By preparing hollow nanorod-shaped iridium oxide catalyst with burr structure in PEM electrolytic technology, the problems of traditional catalysts in inactivation and structural collapse under high oxidation potential are solved, and more efficient catalytic performance and chemical durability are achieved, and manufacturing costs are reduced.

CN115896813BActive Publication Date: 2025-03-04XIAN CATALYST NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211515674.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-30
Publication Date
2025-03-04
Estimated Expiration
2042-11-30

AI Technical Summary

Technical Problem

In the existing PEM electrolytic technology, the selection of anodic oxygen precipitation reaction (OER) catalysts is mainly limited to metal oxides, resulting in catalyst deactivation at high oxidation potentials, increasing manufacturing costs, and the collapse of traditional catalyst structures leads to attenuation of catalytic activity and durability.

Method used

Hollow nanorod-shaped iridium oxide catalyst with burr structure is prepared by hydrothermal, etching, annealing and sintering. Cu2O nanorods are used as sacrificial templates, and hydrothermal treatment and precipitation reaction are used to form a catalyst with hollow, burr and rod-like structures.

Benefits of technology

It improves the catalytic performance and chemical durability of the catalyst, enhances the contact between the surface and internal IrO2 active sites and reactants, promotes the rapid separation of product O2, significantly improves the catalytic activity and durability, and reduces the use of IrO2.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115896813B_ABST
    Figure CN115896813B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a hollow nanorod-shaped iridium oxide catalyst with a burr structure suitable for electrolysis of oxygen in acidic water, comprising the following steps: (1) using copper foil as a substrate, ultrasonically cleaning with dilute hydrochloric acid and pure water; transferring the copper foil to a NaOH solution and immersing it, ice bathing, dripping (NH4)2S2O8 solution, ice bathing, taking out the copper foil, washing it with pure water, annealing, and obtaining Cu2O nanorods grown on the surface of the copper foil; (2) in a hydrothermal kettle, using the Cu2O nanorods grown on the surface of the copper foil as a sacrificial template, adding an iridium salt solution, then adding an NH4F solution and a CH4N2O solution, immersing, performing hydrothermal treatment and precipitation reaction, placing it in a dilute hydrochloric acid solution for ultrasonic treatment, and centrifugal cleaning; (3) roasting, washing after cooling, vacuum drying, and grinding. The method provided by the invention can prepare a hollow nanorod-shaped iridium oxide catalyst with a burr structure, which has good catalytic activity and long chemical durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogen production by water electrolysis, and particularly relates to a method for preparing a hollow nanorod-shaped iridium oxide catalyst with a burr structure suitable for oxygen decomposition by acidic water electrolysis. Background Art

[0002] Hydrogen has become a recognized carrier of ideal energy in the future. It can be produced from traditional fossil fuels such as coal, oil, and natural gas, as well as clean energy such as wind and solar energy. Hydrogen obtained from renewable energy is considered "green hydrogen". Among the many hydrogen production processes, the proton exchange membrane (PEM) technology route has the advantages of simple and easy-to-obtain raw materials, compact structure, high current density, fast startup response, no greenhouse gas emissions, and high purity. In addition, PEM hydrogen production technology is very suitable for linkage with renewable energy sources such as photovoltaics, hydropower, and wind power, converting "abandoned electricity" into chemical energy for storage.

[0003] The electrolysis of water mainly involves two half-reaction processes, the hydrogen evolution reaction (HER) at the cathode and the oxygen evolution reaction (OER) at the anode. Compared with the HER reaction occurring at the cathode, the anode OER reaction process is more loaded and is also the main bottleneck restricting the development of PEM electrolysis technology. The catalytic reaction path of OER usually involves a multi-step multi-electron transfer process, and there are multiple adsorption and desorption processes of oxygen-containing intermediates. As a result, the anode requires a higher overpotential to overcome the reaction energy barrier, so the main energy loss in PEM electrolysis of water comes from the high potential of the anode. Traditional transition metal catalysts are easily deactivated at high oxidation potentials, so the choice of OER catalysts is mainly limited to metal oxides. However, in the OER process, the lattice oxygen on the surface of the metal oxide will directly participate in the reaction. Although this step can reduce the energy barrier of the catalytic reaction, the coupling transfer process between the oxygen-containing functional group and the lattice oxygen will also lead to the collapse of the catalyst structure, resulting in the attenuation of catalytic activity and durability.

[0004] Considering the high oxidation potential during the PEM test, IrO2 is still the catalyst with the best OER performance so far. However, the Ir element is scarce in the earth and is expensive, which increases the cost of PEM water electrolysis. Therefore, how to improve the catalytic performance of IrO2 to reduce the use of IrO2 is a technical difficulty in this field. Summary of the invention

[0005] In view of the defects of the prior art, the present invention provides a method for preparing an iridium oxide catalyst suitable for electrolysis of oxygen in acidic water, which can prepare an iridium oxide catalyst with a hollow nanorod shape and a burr structure, and has uniform phase distribution, good specific surface area, good catalytic activity and long chemical durability.

[0006] A method for preparing a hollow nanorod-shaped iridium oxide catalyst with a burr structure suitable for electrolysis of oxygen in acidic water, comprising the following steps:

[0007] (1) Using copper foil as a substrate, clean it with dilute hydrochloric acid and pure water ultrasonically; then transfer the copper foil to a NaOH solution, place it in an ice bath for 0.5-1h, then add (NH4)2S2O8 solution until the pH of the system is 6-7, continue to place it in an ice bath for 0.5-2h, take out the copper foil, clean it with pure water to obtain a Cu(OH)2 precursor material, and perform annealing under N2 protection to obtain Cu2O nanorods grown on the surface of the copper foil;

[0008] (2) In a hydrothermal reactor, the Cu2O nanorods grown on the surface of the copper foil are used as sacrificial templates, an iridium salt solution is added, and then an NH4F solution and a CH4N2O solution are added, and hydrothermal treatment and precipitation reaction are simultaneously performed to obtain a rod array sample intermediate, which is then placed in a dilute hydrochloric acid solution for ultrasonic treatment and centrifugal washing to obtain a catalyst precursor;

[0009] (3) The catalyst precursor is calcined, cooled, washed with a dilute hydrochloric acid solution, then washed with water until no chloride ions are left in the washing solution, vacuum dried, and ground.

[0010] Preferably, the flow rate of N2 in step (1) is 20-100 sccm, the temperature of the annealing treatment is 300-500°C, and the annealing treatment time is 1-2 h.

[0011] Preferably, the temperature of the hydrothermal treatment in step (2) is 100-120°C and the time is 6-12 h.

[0012] Preferably, the ultrasonic treatment time in step (2) is 1-3 h.

[0013] Preferably, the concentration of the dilute hydrochloric acid in step (1) is 0.5-2 mol / L; the concentration of the dilute hydrochloric acid solution in step (2) is 1-3 mol / L; and the concentration of the dilute hydrochloric acid solution in step (3) is 0.1-0.5 mol / L.

[0014] Preferably, the concentration of the (NH4)2S2O8 solution in step (1) is 0.1-2 mol / L, and the pH of the NaOH solution is 8-10.

[0015] Preferably, the concentration of the iridium salt solution in step (2) is 50-200 mmol / L, and the concentrations of the NH4F solution and the CH4N2O solution are both 0.1-2 mol / L.

[0016] Preferably, the iridium salt is iridium trichloride, iridium tetrachloride, chloroiridic acid, iridium chloride acetate, ammonium iridate or potassium hexachloroiridate.

[0017] Preferably, the calcination conditions in step (3) are: heating to 400-600°C at a heating rate of 2-5°C / min and calcining for 1-3h; and vacuum drying conditions are 50-80°C for 5-10h.

[0018] Advantages of the present invention:

[0019] (1) The present invention obtains a hollow nanorod-shaped iridium oxide catalyst with a burr structure by hydrothermal, etching, annealing and sintering methods. Since the catalyst has a hollow, burr-shaped, rod-shaped structure, the IrO2 active sites on the surface and inside can fully contact the reactants. At the same time, the burr-shaped morphology can promote the rapid separation of the product O2, thereby accelerating the mass transfer process of the catalyst. The nanorod-shaped structure also avoids the problems of catalyst particle agglomeration and difficult morphology control in the prior art.

[0020] (2) The iridium oxide catalyst prepared by the present invention has good catalytic performance and high specific surface area. Compared with the existing commercial IrO2 catalyst, the ECSA is doubled and the current density reaches 10 mAcm -2 The oxygen evolution potential is 270-290 mV, and the catalytic activity is better than that of commercial IrO2 catalyst at the same current density. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 SEM spectrum of the catalyst prepared in Example 2;

[0022] Figure 2 TEM spectrum of the catalyst prepared in Example 2;

[0023] Figure 3 N2 isothermal absorption / desorption curve of the catalyst prepared in Example 2;

[0024] Figure 4 The pore size data distribution diagram of the catalyst prepared in Example 2;

[0025] Figure 5 Polarization current curves of the catalysts prepared in Examples 1-3 and commercial IrO2 catalysts;

[0026] Figure 6 Double layer capacitance values ​​of the catalyst prepared in Example 2 and the commercial IrO2 catalyst. DETAILED DESCRIPTION

[0027] The copper foil selected in the embodiment of the present invention is a 2 cm×3 cm copper foil.

[0028] Example 1

[0029] A method for preparing a hollow nanorod-shaped iridium oxide catalyst with a burr structure suitable for electrolysis of oxygen in acidic water, comprising the following steps:

[0030] (1) Using copper foil as a substrate, 0.5 mol / L dilute hydrochloric acid and pure water were used for ultrasonic cleaning to remove oxide impurities on the surface. The copper foil was then transferred to a NaOH solution with a pH of 9 and immersed in an ice bath for 0.5 h. Then, 1 mol / L (NH4)2S2O8 solution was added dropwise until the pH of the system reached 6. The ice bath was continued for 0.5 h. The copper foil was taken out and cleaned with pure water to obtain a Cu(OH)2 precursor material. The Cu(OH)2 precursor material was placed in a tube furnace and annealed at 400°C for 1 h under the protection of a N2 atmosphere with a flow rate of 50 sccm to obtain Cu2O nanorods grown on the surface of the copper foil.

[0031] (2) In a hydrothermal reactor, the Cu2O nanorods grown on the surface of the copper foil are used as sacrificial templates, 10 mL of 50 mmol / L IrCl3 solution is added, and then 10 mL of 0.2 mol / L NH4F solution and 10 mL of 0.2 mol / L CH4N2O solution are added, and hydrothermal treatment is carried out at 120°C for 10 h to simultaneously carry out precipitation reaction to obtain a rod-shaped array sample intermediate, which is then placed in a 1 mol / L dilute hydrochloric acid solution for ultrasonic treatment for 1 h. Since the acid etches the excess Cu2O, the nanorods present a hollow burr structure and fall off the copper foil as a whole, and are centrifuged and cleaned to obtain a catalyst precursor;

[0032] (3) The catalyst precursor is placed in a muffle furnace, heated to 400°C at a heating rate of 5°C / min, and calcined at 400°C for 2 h. After cooling, it is first washed with a 0.1 mol / L dilute hydrochloric acid solution, and then washed with water until there is no chloride ion in the washing liquid. It is then dried at 50°C in a vacuum for 5 h, ground and stored for later use.

[0033] Example 2

[0034] In step (3), the calcination temperature is 500° C., and the rest is the same as in Example 1.

[0035] Example 3

[0036] In step (3), the calcination temperature is 600° C., and the rest is the same as in Example 1.

[0037] Example 4

[0038] A method for preparing a hollow nanorod-shaped iridium oxide catalyst with a burr structure suitable for electrolysis of oxygen in acidic water, comprising the following steps:

[0039] (1) Using copper foil as a substrate, the copper foil was ultrasonically cleaned with 2 mol / L dilute hydrochloric acid and pure water to remove oxide impurities on the surface. The copper foil was then transferred to a NaOH solution with a pH of 10 and immersed in an ice bath for 1 hour. Then, 0.1 mol / L (NH4)2S2O8 solution was added dropwise until the pH of the system reached 7. The ice bath was continued for 2 hours. The copper foil was taken out and cleaned with pure water to obtain a Cu(OH)2 precursor material. The Cu(OH)2 precursor material was placed in a tube furnace and annealed at 300 °C for 2 hours under the protection of a N2 atmosphere with a flow rate of 20 sccm to obtain Cu2O nanorods grown on the surface of the copper foil.

[0040] (2) In a hydrothermal reactor, the Cu2O nanorods grown on the surface of the copper foil are used as sacrificial templates, 10 mL of 100 mmol / L IrCl3 solution is added, and then 10 mL of 0.1 mol / L NH4F solution and 10 mL of 0.1 mol / L CH4N2O solution are added, and hydrothermal treatment is carried out at 100°C for 12 h to simultaneously carry out precipitation reaction to obtain a rod-shaped array sample intermediate, which is then placed in a 3 mol / L dilute hydrochloric acid solution for ultrasonic treatment for 0.5 h. Since the acid etches the excess Cu2O, the nanorods present a hollow burr structure and fall off the copper foil as a whole, and are centrifuged and cleaned to obtain a catalyst precursor;

[0041] (3) The catalyst precursor is placed in a muffle furnace, heated to 500°C at a heating rate of 5°C / min, and calcined at 500°C for 1 hour. After cooling, it is first washed with a 0.5 mol / L dilute hydrochloric acid solution, and then washed with water until there is no chloride ion in the washing liquid. It is then dried at 50°C in a vacuum for 10 hours, ground and stored for later use.

[0042] Example 5

[0043] A method for preparing a hollow nanorod-shaped iridium oxide catalyst with a burr structure suitable for electrolysis of oxygen in acidic water, comprising the following steps:

[0044] (1) Using copper foil as a substrate, the copper foil was ultrasonically cleaned with 2 mol / L dilute hydrochloric acid and pure water to remove oxide impurities on the surface. The copper foil was then transferred to a NaOH solution with a pH of 9 and placed in an ice bath for 1 hour. Then, a 2 mol / L (NH4)2S2O8 solution was added dropwise until the pH of the system reached 6. The ice bath was continued for 1 hour. The copper foil was taken out and cleaned with pure water to obtain a Cu(OH)2 precursor material. The Cu(OH)2 precursor material was placed in a tube furnace and annealed at 500°C for 1 hour under a N2 atmosphere with a flow rate of 100 sccm to obtain Cu2O nanorods grown on the surface of the copper foil.

[0045] (2) In a hydrothermal reactor, the Cu2O nanorods grown on the surface of the copper foil are used as sacrificial templates, 10 mL of 200 mmol / L IrCl3 solution is added, and then 10 mL of 2 mol / L NH4F solution and 10 mL of 2 mol / L CH4N2O solution are added, and hydrothermal treatment is carried out at 120°C for 6 h to simultaneously perform precipitation reaction to obtain a rod-shaped array sample intermediate, which is then placed in a 2 mol / L dilute hydrochloric acid solution for ultrasonic treatment for 1 h. Since the acid etches the excess Cu2O, the nanorods present a hollow burr structure and fall off the copper foil as a whole, and are centrifuged and cleaned to obtain a catalyst precursor;

[0046] (3) The catalyst precursor is placed in a muffle furnace, heated to 500°C at a heating rate of 5°C / min, and calcined at 400°C for 4 hours. After cooling, it is first washed with a 0.2 mol / L dilute hydrochloric acid solution, and then washed with water until there is no chloride ion in the washing liquid. It is then dried at 80°C in a vacuum for 5 hours, ground and stored for later use.

[0047] Performance Testing

[0048] 1. SEM and TEM inspection

[0049] The iridium oxide catalyst obtained in Example 2 was subjected to SEM and TEM examinations. Figure 1 and Figure 2 ,Depend on Figure 1 It can be seen that the iridium oxide catalyst obtained by the present invention is a uniform nanorod-like burr structure with a diameter ranging from 100 to 300 nm. Figure 2 It can be observed that the iridium oxide catalyst obtained in the present invention has a hollow structure, and there are burr structures with a length of 50-100 nm and a width of 5-10 nm on the surface.

[0050] 2. N2 isothermal adsorption / desorption detection

[0051] Figure 3 The N2 isothermal adsorption / desorption curve of the iridium oxide catalyst prepared in Example 2. It can be seen that the curve is a typical type IV characteristic isotherm, with the following features: convex in the low-pressure region, capillary condensation in the high-pressure region, non-overlapping adsorption and desorption, and the presence of a process adsorption hysteresis loop, indicating that the composite material has an obvious mesoporous distribution. The BET specific surface area of ​​the sample is 201.45 m 2 / g.

[0052] 3. Pore size distribution detection

[0053] The iridium oxide catalyst prepared in Example 2 was subjected to a physical and chemical adsorption test to obtain pore size distribution data. The pore size data distribution diagram is shown in FIG. Figure 4 .Depend on Figure 4 It can be seen that the pore diameters are mostly distributed around 10 nm.

[0054] 4. Electrochemical Characterization

[0055] 4.1 Polarization current curve

[0056] The polarization current curves of Examples 1-3 and commercial IrO2 catalysts are shown in Figure 5 ,Depend on Figure 5 It can be seen that the iridium oxide catalysts obtained in Examples 1, 2, and 3 have a current density of 10 mAcm -2 When the overpotentials are 292 mV, 280 mV and 308 mV respectively, the catalytic activity is better than that of the commercial IrO2 (320 mV) catalyst at the same current density. Among Examples 1-3, the catalyst obtained by calcining at 500 °C in Example 2 has the best catalytic activity.

[0057] 4.2 Electrochemically active surface area (ECSA)

[0058] Figure 6 is the double-layer capacitance of the iridium oxide catalyst obtained in Example 2 and the commercial IrO2 catalyst ( C dl ), wherein the iridium oxide catalyst obtained in Example 2 and the commercial IrO2 catalyst C dl 38.3 and 18.7 mFcm respectively -2 , usually, the ECSA value of a catalyst can be obtained by C dl With oxide surface capacitance (40 μFcm -2 ) ratio, and the ECSA value of the iridium oxide catalyst obtained in Example 2 and commercial IrO2 was calculated to be 0.096 m 2 and 0.047 m 2 , indicating that the IrO2 catalyst of Example 2 of the present invention has more electrochemical active sites and can efficiently utilize the IrO2 active sites.

Claims

1. A method for preparing a hollow nanorod-shaped iridium oxide catalyst with a burr structure suitable for electrolysis of oxygen in acidic water, characterized in that: The following steps are involved: (1) Using copper foil as the substrate, ultrasonic cleaning is performed with dilute hydrochloric acid and pure water; Subsequently, the copper foil was transferred to a NaOH solution and immersed in an ice bath for 0.5-1 h, and then (NH4)2S2O8 solution was added dropwise until the pH of the system was 6-7, and the ice bath was continued for 0.5-2 h. The copper foil was taken out and washed with pure water to obtain a Cu(OH)2 precursor material, which was annealed under N2 protection to obtain Cu2O nanorods grown on the surface of the copper foil; (2) In a hydrothermal reactor, the Cu2O nanorods grown on the surface of the copper foil are used as sacrificial templates, an iridium salt solution is added, and then an NH4F solution and a CH4N2O solution are added to immerse the Cu2O nanorods grown on the surface of the copper foil, and hydrothermal treatment and precipitation reaction are simultaneously performed to obtain a rod-shaped array sample intermediate, which is then placed in a dilute hydrochloric acid solution for ultrasonic treatment. Since the acid etches the excess Cu2O, the nanorods present a hollow burr structure and fall off the copper foil as a whole, and are centrifuged and cleaned to obtain a catalyst precursor; (3) The catalyst precursor is calcined, cooled, washed with a dilute hydrochloric acid solution, then washed with water until no chloride ions are left in the washing solution, vacuum dried, and ground.

2. The method for preparing a hollow nanorod-shaped iridium oxide catalyst with a burr structure suitable for electrolysis of oxygen in acidic water according to claim 1, characterized in that: In step (1), the flow rate of N2 is 20-100 sccm, the temperature of the annealing treatment is 300-500°C, and the annealing treatment time is 1-2 h.

3. The method for preparing a hollow nanorod-shaped iridium oxide catalyst with a burr structure suitable for electrolysis of oxygen in acidic water according to claim 2, characterized in that: The temperature of the hydrothermal treatment in step (2) is 100-120°C and the time is 6-12 h.

4. The method for preparing a hollow nanorod-shaped iridium oxide catalyst with a burr structure suitable for electrolysis of oxygen in acidic water according to claim 3, characterized in that: The ultrasonic treatment time in step (2) is 1-3 hours.

5. The method for preparing a hollow nanorod-shaped iridium oxide catalyst with a burr structure suitable for electrolysis of oxygen in acidic water according to claim 4, characterized in that: The concentration of the dilute hydrochloric acid in step (1) is 0.5-2 mol / L; the concentration of the dilute hydrochloric acid solution in step (2) is 1-3 mol / L; the concentration of the dilute hydrochloric acid solution in step (3) is 0.1-0.5 mol / L.

6. The method for preparing a hollow nanorod-shaped iridium oxide catalyst with a burr structure suitable for electrolysis of oxygen in acidic water according to claim 5, characterized in that: The concentration of the (NH4)2S2O8 solution in step (1) is 0.1-2 mol / L, and the pH of the NaOH solution is 8-10.

7. The method for preparing the hollow nanorod-shaped iridium oxide catalyst with a burr structure suitable for electrolysis of oxygen in acidic water according to claim 6, characterized in that: In step (2), the concentration of the iridium salt solution is 50-200 mmol / L, and the concentrations of the NH4F solution and the CH4N2O solution are both 0.1-2 mol / L.

8. The method for preparing the hollow nanorod-shaped iridium oxide catalyst with a burr structure suitable for electrolysis of oxygen in acidic water according to claim 7, characterized in that: The iridium salt is iridium trichloride, iridium tetrachloride, chloroiridic acid, iridium chloride acetate, ammonium iridate or potassium hexachloroiridate.

9. The method for preparing the hollow nanorod-shaped iridium oxide catalyst with a burr structure suitable for electrolysis of oxygen in acidic water according to claim 8, characterized in that: The calcination conditions in step (3) are: heating to 400-600°C at a heating rate of 2-5°C / min and calcining for 1-3h; and vacuum drying at 50-80°C for 5-10h.

Citation Information

Patent Citations

  • Single oriented iridium oxide nano array preparation and membrane electrode construction method

    CN107490652A

  • Method for rapidly preparing high-activity array hydrogen evolution catalyst

    CN111939913A